2D MOF Nanoflake-Assembled Spherical Microstructures for Enhanced Supercapacitor and Electrocatalysis Performances - Xia, Huicong; Zhang, Jianan; Yang, Zhao; Guo, Shiyu; Guo, Shihui; Xu, Qun (Nano-Micro Letters, 2017)
Metal–organic frameworks (MOFs) are of great interest as potential electrochemically active materials. However, few studies have been conducted into understanding whether control of the shape and components of MOFs can optimize their electrochemical performances due to the rational realization of their shapes. Component control of MOFs remains a significant challenge. Herein, we demonstrate a solvothermal method to realize nanostructure engineering of 2D nanoflake MOFs. The hollow structures with Ni/Co- and Ni-MOF (denoted as Ni/Co-MOF nanoflakes and Ni-MOF nanoflakes) were assembled for their electrochemical performance optimizations in supercapacitors and in the oxygen reduction reaction (ORR). As a result, the Ni/Co-MOF nanoflakes exhibited remarkably enhanced performance with a specific capacitance of 530.4 F g−1 at 0.5 A g−1 in 1 M LiOH aqueous solution, much higher than that of Ni-MOF (306.8 F g−1) and ZIF-67 (168.3 F g−1), a good rate capability, and a robust cycling performance with no capacity fading after 2000 cycles. Ni/Co-MOF nanoflakes also showed improved electrocatalytic performance for the ORR compared to Ni-MOF and ZIF-67. The present work highlights the significant role of tuning 2D nanoflake ensembles of Ni/Co-MOF in accelerating electron and charge transportation for optimizing energy storage and conversion devices. Highlights: 1 A solvothermal method was used to improve the conductivity and electrochemical activity of metal–organic framework (MOF) materials by tuning their morphology and components. 2 Ni/Co-MOF nanoflakes exhibit remarkably enhanced performances including enhanced electrocatalytic performance for the oxygen reduction reaction. 3 The synthetic strategy driven by rational design gives the first example of exploring MOF-derived nanomaterials to achieve improved efficiency energy storage and conversion devices.